Food systems science for peace and security: Is research for development key for achieving systematic change? - Theresa Liebig; Grazia Pacillo; Diego Osorio; Peter Läderach (World Development Sustainability, 2022)
This paper uses CGIAR research as an example to demonstrate the potential of food systems science to contribute to conflict prevention and peacebuilding. Conflict often arises through a complex process whose triggers and consequences are closely interconnected in feedback loops and linked to climate variability, environmental degradation and food insecurity. Conflicts are often approached from a symptomatic rather than a holistic perspective. We (i) review the literature on climate security to identify conflict pathways and related drivers. This serves as the basis for mapping CGIAR and partner research related to climate security through a portfolio review (ii) and facilitated multidisciplinary expert panel discussions (iii). We then define cross-cutting priorities for the future direction of climate security debates, policies and programmes and link them to the new One CGIAR strategy. Conflicts pathways related to food systems, migration and weak governance were among the most studied conflict drivers found in the literature. The same drivers are also frequently studied by CGIAR and addressed by conveying knowledge and tools on disaster- risk reduction, climate change adaptation and livelihood resilience, among others. Four cross-cutting priorities for peacebuilding emerged from the panel discussions: (1) integrating food systems science into policy conversations; (2) bridging the gap between food systems science and security through data and new technologies; (3) financing to build sustainable livelihoods for conflict-affected populations; and (4) multidisciplinary partnerships. CGIAR, its many partners and partner research and development initiatives, are well positioned to demonstrate the potential of food systems science to contribute to peacebuilding.